Development and preparation process of high-glossiness transparent crystal glaze material
By combining specific geological materials and multi-stage temperature-controlled sintering technology, a high-gloss permeable crystal glaze was developed, which solved the problems of unstable gloss and insufficient thermal shock resistance of traditional gloss, and achieved high translucency and resistance. Abrasiveness, excellent color rendering effect, and meets national standards.
Patent Information
- Application Number
- CN202410800654.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2024-12-27
AI Technical Summary
When traditional transparent glaze is used on ceramics, it has unstable gloss and low transparency, which is prone to bubbles and cracks, and has insufficient thermal shock resistance.
Develop a high-gloss permeable crystal glaze, through the combination of materials such as Hezhou Potassium feldspar, Yulin limestone in Guangxi, Guangxi, Guixi, and Gaozhou kaolin in Guangdong, using wet ball milling and multi-stage temperature-controlled sintering technology , prepare high gloss and high transmissivity glaze to ensure that the glaze surface is crystal clear and wear-resistant.
It achieves high gloss and high translucency of the glaze, delicate and bright glaze, product has no bubbles, good thermal shock resistance, meets national standards, and zero lead and cadmium dissolution detection is used to detect lead and cadmium dissolution, adapts to microwave ovens, and color development Excellent effect.
Smart Images

Figure CN119191711A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic preparation, and in particular to a development and production process of a high-gloss transparent crystal glaze. Background Art
[0002] The glazes used in ceramic preparation technology are becoming more and more diverse. They can be roughly classified into lead glaze and lead-free glaze, raw material glaze and frit glaze, and glaze for single firing or double firing. According to the glazing method, they are also divided into dipping glaze, spraying glaze, and pouring glaze. There are also various pursuits in the color pattern and light sensitivity of the glaze, including colored glaze and colorless glaze, transparent glaze and opalescent glaze, glossy glaze, matte glaze, semi-matte glaze or patterned glaze, etc. Underglaze color is a major decorative method for ceramics. It is to draw various patterns on the formed and dried blank (i.e. semi-finished product) with colorants, and then cover it with transparent glaze or other light-colored glaze, and fire it once. The fired pattern is covered with a layer of transparent glaze underneath, and the surface is bright, soft, smooth and not protruding, and appears crystal clear.
[0003] Transparent glazes that can be used in the production of underglaze colors have the characteristics of high transparency, high gloss, and bright colors. They are widely used in various ceramic products. The traditional underglaze color process has been popular in China for thousands of years. Most of its production processes are to decorate the blank first and then apply the traditional transparent glaze. The glaze effect of the traditional transparent glaze is unstable, the transparency is not high, the gloss is not strong, and the product is prone to bubbles and cracks. Therefore, it is urgent to research and develop a high-gloss transparent crystal glaze that can be used in the production of underglaze colors, which can achieve high gloss and high transparency of the glaze, and the glaze surface is crystal clear, glass-like and transparent, delicate and bright, and the product does not produce bubbles. The glaze surface is hard and wear-resistant, and has good thermal shock resistance. Summary of the invention
[0004] In view of the above deficiencies, the present invention provides a development and production process of a high-gloss translucent crystal glaze, which can achieve high gloss and high transmittance of the product, and the glaze surface is crystal clear, delicate and bright. It can be applied to underglaze printing and underglaze colorful crafts to make the underglaze color bright and bright, and the product does not produce any bubbles; at the same time, it can also achieve thermal shock resistance detection at 180℃-20℃ without cracking once, which meets the national standard; microwave oven adaptability detection once cycle without cracking and no arc generation; the product can also achieve zero lead and cadmium dissolution after lead and cadmium dissolution detection, which is far lower than the national standard.
[0005] The specific technical solutions are as follows:
[0006] The invention provides a high-gloss transparent crystal glaze, which is composed of the following mass percentages: 19-22% of potassium feldspar from Hezhou, Guangxi, 4-7% of limestone from Yulin, Guangxi, 61-65% of transparent crystal frit from Luxi City, Guangxi, 3-8% of clay, and 3-8% of Gaozhou clay from Guangdong.
[0007] Preferably, the high-gloss translucent crystal glaze is composed of the following mass percentages: 20% potassium feldspar from Hezhou, Guangxi, 6% limestone from Yulin, Guangxi, 63% transparent crystal frit from Luxi City, Guangxi, 5% clay, and 6% high-altitude clay from Gaozhou, Guangdong.
[0008] The potassium feldspar in Hezhou, Guangxi is potassium feldspar produced in Hezhou City, Guangxi; the limestone in Yulin, Guangxi is calcined limestone produced in Yulin City, Guangxi; the transparent crystal frit in Cenxi City, Guangxi is transparent crystal frit produced in Cenxi City, Guangxi; and the Gaozhou kaolin is kaolin produced in Gaozhou City, Guangdong.
[0009] Preferably, the chemical composition of the Guangxi Hezhou potassium feldspar is as follows in percentage by mass: 69.08% silicon oxide, 17.63% aluminum oxide, 0.12% iron oxide, 0.01% titanium dioxide, 0.51% calcium oxide, 0.13% magnesium oxide, 10.25% potassium oxide, 2.21% sodium oxide, and 0.06% loss on ignition.
[0010] Preferably, the chemical composition of the transparent crystal frit from Guxi City, Guangxi is as follows in percentage by mass: 65.85% silicon oxide, 6.42% aluminum oxide, 0.21% iron oxide, 0.01% titanium dioxide, 13.82% calcium oxide, 3.03% magnesium oxide, 2.50% potassium oxide, 1.60% sodium oxide, 2.32% zinc oxide, 1.11% boron oxide, 3.02% barium oxide, and 0.11% ignition loss.
[0011] Preferably, the chemical composition of the Guangxi Yulin limestone is as follows in percentage by mass: 2.1% silicon oxide, 0.15% aluminum oxide, 0.06% iron oxide, 0.01% titanium dioxide, 56.17% calcium oxide, 0.03% magnesium oxide, 0.11% potassium oxide, 0.09% sodium oxide, and ignition loss of 41.28%.
[0012] Preferably, the chemical composition of the Guangdong Gaozhou kaolin is as follows in percentage by mass: 53.57% silicon oxide, 35.32% aluminum oxide, 0.15% iron oxide, 0.03% titanium dioxide, 0.17% calcium oxide, 0.06% magnesium oxide, 0.21% potassium oxide, 0.15% sodium oxide, and 10.16% loss on ignition.
[0013] Preferably, it is characterized in that the chemical composition of the clay is as follows in percentage by mass: 62.29% silicon oxide, 23.5% aluminum oxide, 0.19% iron oxide, 0.01% titanium dioxide, 1.35% calcium oxide, 3.21% magnesium oxide, 3.26% potassium oxide, 1.13% sodium oxide, and 5.06% loss on ignition.
[0014] The present invention also provides a process for producing a high-gloss transparent crystal glaze, comprising the following steps:
[0015] (1) putting the glaze raw materials of the above composition into a wet ball mill according to each component, discharging the slurry, and passing through a 200-300 mesh sieve to obtain a primary material;
[0016] (2) The raw material is passed through a magnetic separator to remove iron, thereby obtaining a high-gloss, transparent crystal glaze.
[0017] The present invention also provides a method for using a high-gloss transparent crystal glaze, comprising the following steps:
[0018] (1) trimming, hydrating and drying the dry blank to obtain a blank;
[0019] (2) Printing or drawing colored patterns on the blank and drying it;
[0020] (3) dipping the blank with the pattern printed thereon with the high-gloss transparent crystal glaze for 3-4 seconds to obtain a glaze blank, wiping off the glaze accumulated at the foot of the glaze blank, and checking that the glaze blank has no defects to obtain a prefabricated glaze blank;
[0021] (4) placing the prefabricated glaze blank into a sintering furnace, and sintering the prefabricated glaze blank in a multi-stage temperature-controlled sintering process, including a low temperature stage, a first medium temperature stage, a second medium temperature stage, a high temperature stage, a rapid cooling stage, and a slow cooling stage;
[0022] (5) The sintered glaze blanks are graded and numbered, and packaged for shipment.
[0023] Preferably, the firing temperature of the prefabricated glaze blank is controlled at 1250-1280° C. and fired in an oxidizing atmosphere.
[0024] Preferably, the thickness of the glaze layer in the above step (3) is controlled to be 0.2-0.4 mm.
[0025] Preferably, the multi-stage temperature control process specifically includes:
[0026] (1) Low temperature stage: the preheating stage of the glaze blank, the kiln temperature is 350-480℃, and the insulation time is 1.8-2.2h;
[0027] (2) The first medium temperature stage is a weak oxidation stage, the kiln temperature is 800-870℃, and the insulation time is 1.5-2.0h;
[0028] (3) The second medium temperature stage is the strong oxidation stage, the kiln temperature is 980-1050℃, and the insulation time is 2.5-3.0h;
[0029] (4) High temperature stage: the glaze vitrification stage of the product, the kiln temperature is 1260-1280℃, and the control time is 1.5-2.0h;
[0030] (5) Rapid cooling stage is the key stage for controlling the glaze surface of the product. The kiln temperature is 1280-800℃ and the control time is 1.2-1.5h;
[0031] (6) Slow cooling stage, the kiln temperature is 800-580℃, and the insulation time is 2.0-2.5h;
[0032] (7) Wait for natural cooling to complete the firing process.
[0033] Preferably, the glaze fineness controls the residue on a 10,000-mesh sieve to be between 0.016 and 0.02.
[0034] Preferably, the glaze concentration is controlled at 46-48 degrees Baume.
[0035] Preferably, the glaze specific gravity is controlled at 1.45-1.48.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] 1. The glaze of the present invention makes full use of transparent frits and other raw materials in nearby areas. It can achieve high gloss and high transparency of the glaze at a relatively low cost in combination with a multi-stage temperature-controlled production process. The glaze surface is crystal clear, delicate and bright. It can be applied to underglaze printing and underglaze multi-color technology, making the underglaze multi-color color highly transparent without bubbles and cracks.
[0038] 2. The method for using the glaze of the present invention adopts a multi-stage temperature-controlled sintering process. The prepared glaze is glass-like and transparent, delicate and bright, with high gloss and high transmittance, and has an excellent coloring effect on underglaze colors. The colors of the underglaze colors that are refracted and transmitted are brighter and more colorful; at the same time, it can also achieve thermal shock resistance testing at 180°C-20°C without cracking once, which meets national standards; microwave oven adaptability testing shows no cracking and no arcing in one cycle; the product can also achieve zero lead and cadmium dissolution after lead and cadmium dissolution testing, which is far lower than national standards.
[0039] 3. The glaze fineness of the present invention controls the sieve residue to be 0.016-0.02, the glaze concentration to be 46-48 degrees Baume, and the glaze water specific gravity to be 1.45-1.48, so that no bubbles are generated on the glaze surface, the turbidity is reduced, and a transparent and delicate texture is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.
[0041] Figure 1 This is a product use effect diagram of the high-gloss transparent crystal glaze in Example 1 of the present invention;
[0042] Figure 2This is a product use effect diagram of the high-gloss transparent crystal glaze in Example 2 of the present invention;
[0043] Figure 3 This is a product usage effect diagram of the high-gloss transparent crystal glaze in Example 3 of the present invention. DETAILED DESCRIPTION
[0044] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.
[0045] Example 1
[0046] The high-gloss transparent crystal glaze of this embodiment is composed of the following mass percentages: 22% potassium feldspar from Hezhou, Guangxi, 7% limestone from Yulin, Guangxi, 65% transparent crystal frit from Luxi City, Guangxi, 3% clay, and 3% high-altitude clay from Gaozhou, Guangdong.
[0047] The potassium feldspar in Hezhou, Guangxi is potassium feldspar produced in Hezhou City, Guangxi; the limestone in Yulin, Guangxi is calcined limestone produced in Yulin City, Guangxi; the transparent crystal frit in Cenxi City, Guangxi is transparent crystal frit produced in Cenxi City, Guangxi; and the Gaozhou kaolin is kaolin produced in Gaozhou City, Guangdong.
[0048] The chemical composition of the Guangxi Hezhou potassium feldspar is as follows in percentage by mass: 69.08% silicon oxide, 17.63% aluminum oxide, 0.12% iron oxide, 0.01% titanium dioxide, 0.51% calcium oxide, 0.13% magnesium oxide, 10.25% potassium oxide, 2.21% sodium oxide, and 0.06% loss on ignition.
[0049] The chemical composition of the transparent crystal frit in Guxi City, Guangxi Province is as follows in percentage by mass: 65.85% silicon oxide, 6.42% aluminum oxide, 0.21% iron oxide, 0.01% titanium dioxide, 13.82% calcium oxide, 3.03% magnesium oxide, 2.50% potassium oxide, 1.60% sodium oxide, 2.32% zinc oxide, 1.11% boron oxide, 3.02% barium oxide, and 0.11% ignition loss.
[0050] The chemical composition of the Guangxi Yulin limestone is as follows in percentage by weight: 2.1% silicon oxide, 0.15% aluminum oxide, 0.06% iron oxide, 0.01% titanium dioxide, 56.17% calcium oxide, 0.03% magnesium oxide, 0.11% potassium oxide, 0.09% sodium oxide, and ignition loss is 41.28%.
[0051] The chemical composition of the Guangdong Gaozhou kaolin is as follows in percentage by weight: 53.57% silicon oxide, 35.32% aluminum oxide, 0.15% iron oxide, 0.03% titanium dioxide, 0.17% calcium oxide, 0.06% magnesium oxide, 0.21% potassium oxide, 0.15% sodium oxide, and 10.16% loss on ignition.
[0052] The chemical composition of the clay is as follows in percentage by weight: 62.29% silicon oxide, 23.5% aluminum oxide, 0.19% iron oxide, 0.01% titanium dioxide, 1.35% calcium oxide, 3.21% magnesium oxide, 3.26% potassium oxide, 1.13% sodium oxide, and 5.06% loss on ignition.
[0053] The manufacturing process of the high-gloss transparent crystal glaze of this embodiment includes the following steps:
[0054] (1) putting the glaze raw materials of the above composition into a wet ball mill according to each component, grinding them, releasing the slurry, and passing through a 300-mesh sieve to obtain a primary material;
[0055] (2) The primary material is passed through a magnetic separator to remove iron, and the glaze fineness is controlled to be between 0.02 on a 10,000-hole sieve, thereby obtaining a high-gloss, transparent crystal glaze.
[0056] The method for using the high-gloss transparent crystal glaze of this embodiment comprises the following steps:
[0057] (1) trimming, hydrating and drying the dry blank to obtain a blank;
[0058] (2) Printing or drawing colored patterns on the blank and drying it;
[0059] (3) using the high-gloss transparent crystal glaze to glaze the blank with the pattern printed on it, the glazing time is 4 seconds, the thickness of the glaze layer is controlled at 0.4 mm, and a glaze blank is obtained. The glaze at the foot of the glaze blank is wiped clean, and the glaze blank is checked to be free of defects to obtain a prefabricated glaze blank; the glaze concentration is controlled at 48 degrees Baume, and the glaze water specific gravity is controlled at 1.48;
[0060] (4) The prefabricated glaze blank is placed in a sintering furnace and sintered in a multi-stage temperature-controlled manner. The low-temperature stage is the preheating stage of the glaze blank, the kiln temperature is 350°C, and the insulation time is 2.2 hours; the first medium-temperature stage is the weak oxidation stage, the kiln temperature is 800°C, and the insulation time is 2.0 hours; the second medium-temperature stage is the strong oxidation stage, the kiln temperature is 980°C, and the insulation time is 3.0 hours; the high-temperature stage is the vitrification stage of the product glaze, the kiln temperature is 1260°C, and the insulation time is 2.0 hours; the rapid cooling stage is the key stage for controlling the product glaze, the kiln temperature is 1280-800°C, and the control time is 1.5 hours; the slow cooling stage, the kiln temperature is 800-580°C, and the control time is 2.5 hours; wait for natural cooling to complete the firing process and obtain the product, and the use effect is as follows: Figure 1 shown.
[0061] Example 2
[0062] The high-gloss translucent crystal glaze of this embodiment is composed of the following mass percentages: 19% potassium feldspar from Hezhou, Guangxi, 4% limestone from Yulin, Guangxi, 61% transparent crystal frit from Luxi City, Guangxi, 8% clay, and 8% high-altitude clay from Gaozhou, Guangdong.
[0063] The potassium feldspar of Hezhou, Guangxi is potassium feldspar produced in Hezhou, Guangxi; the limestone of Yulin, Guangxi is calcined limestone produced in Yulin, Guangxi; the transparent crystal frit of Cenxi, Guangxi is transparent crystal frit produced in Cenxi, Guangxi; the kaolin of Gaozhou is kaolin produced in Gaozhou, Guangdong;
[0064] The chemical composition of the Guangxi Hezhou potassium feldspar is as follows in percentage by mass: 69.08% silicon oxide, 17.63% aluminum oxide, 0.12% iron oxide, 0.01% titanium dioxide, 0.51% calcium oxide, 0.13% magnesium oxide, 10.25% potassium oxide, 2.21% sodium oxide, and 0.06% loss on ignition.
[0065] The chemical composition of the transparent crystal frit in Guxi City, Guangxi Province is as follows in percentage by mass: 65.85% silicon oxide, 6.42% aluminum oxide, 0.21% iron oxide, 0.01% titanium dioxide, 13.82% calcium oxide, 3.03% magnesium oxide, 2.50% potassium oxide, 1.60% sodium oxide, 2.32% zinc oxide, 1.11% boron oxide, 3.02% barium oxide, and 0.11% ignition loss.
[0066] The chemical composition of the Guangxi Yulin limestone is as follows in percentage by weight: 2.1% silicon oxide, 0.15% aluminum oxide, 0.06% iron oxide, 0.01% titanium dioxide, 56.17% calcium oxide, 0.03% magnesium oxide, 0.11% potassium oxide, 0.09% sodium oxide, and ignition loss is 41.28%.
[0067] The chemical composition of the Guangdong Gaozhou kaolin is as follows in percentage by weight: 53.57% silicon oxide, 35.32% aluminum oxide, 0.15% iron oxide, 0.03% titanium dioxide, 0.17% calcium oxide, 0.06% magnesium oxide, 0.21% potassium oxide, 0.15% sodium oxide, and 10.16% loss on ignition.
[0068] The chemical composition of the clay is as follows in percentage by weight: 62.29% silicon oxide, 23.5% aluminum oxide, 0.19% iron oxide, 0.01% titanium dioxide, 1.35% calcium oxide, 3.21% magnesium oxide, 3.26% potassium oxide, 1.13% sodium oxide, and 5.06% loss on ignition.
[0069] The manufacturing process of the high-gloss transparent crystal glaze of this embodiment includes the following steps:
[0070] (1) putting the glaze raw materials of the above composition into a wet ball mill according to each component, grinding them, releasing the slurry, and passing through a 200-mesh sieve to obtain a primary material;
[0071] (2) The primary material is passed through a magnetic separator to remove iron, and the glaze fineness is controlled to have a sieve residue of 0.016, thereby obtaining a high-gloss, translucent crystal glaze.
[0072] The method for using the high-gloss transparent crystal glaze of this embodiment comprises the following steps:
[0073] (1) trimming, hydrating and drying the dry blank to obtain a blank;
[0074] (2) Printing or drawing colored patterns on the blank and drying it;
[0075] (3) using the high-gloss transparent crystal glaze to glaze the blank with the pattern printed on it, the glazing time is 3 seconds, the thickness of the glaze layer is controlled at 0.2 mm, and a glaze blank is obtained. The glaze at the foot of the glaze blank is wiped clean, and the glaze blank is checked to be free of defects, so as to obtain a prefabricated glaze blank; the glaze concentration is controlled at 46 degrees Baume, and the glaze water specific gravity is controlled at 1.45;
[0076] (4) The prefabricated glaze blank is placed in a sintering furnace and sintered under multi-stage temperature control. The low temperature stage is the preheating stage of the glaze blank, the kiln temperature is 480°C, and the insulation time is 1.8 hours; the first medium temperature stage is the weak oxidation stage, the kiln temperature is 870°C, and the insulation time is 1.5 hours; the second medium temperature stage is the strong oxidation stage, the kiln temperature is 1050°C, and the insulation time is 2.5 hours; the high temperature stage is the vitrification stage of the product glaze, the kiln temperature is 1280°C, and the insulation time is 1.5 hours; the rapid cooling stage is the key stage for controlling the product glaze, the kiln temperature is 1280-800°C, and the control time is 1.2 hours; the slow cooling stage, the kiln temperature is 800-580°C, and the control time is 2.0 hours; wait for natural cooling to complete the firing process, and obtain the product use effect as shown in the following figure: Figure 2 shown.
[0077] Example 3
[0078] The high-gloss transparent crystal glaze of this embodiment is composed of the following mass percentages: 20% potassium feldspar from Hezhou, Guangxi, 6% limestone from Yulin, Guangxi, 63% transparent crystal frit from Luxi City, Guangxi, 5% clay, and 6% high-altitude clay from Gaozhou, Guangdong.
[0079] The potassium feldspar of Hezhou, Guangxi is potassium feldspar produced in Hezhou, Guangxi; the limestone of Yulin, Guangxi is calcined limestone produced in Yulin, Guangxi; the transparent crystal frit of Cenxi, Guangxi is transparent crystal frit produced in Cenxi, Guangxi; the kaolin of Gaozhou is kaolin produced in Gaozhou, Guangdong;
[0080] The chemical composition of the Guangxi Hezhou potassium feldspar is as follows in percentage by mass: 69.08% silicon oxide, 17.63% aluminum oxide, 0.12% iron oxide, 0.01% titanium dioxide, 0.51% calcium oxide, 0.13% magnesium oxide, 10.25% potassium oxide, 2.21% sodium oxide, and 0.06% loss on ignition.
[0081] The chemical composition of the transparent crystal frit in Guxi City, Guangxi Province is as follows in percentage by mass: 65.85% silicon oxide, 6.42% aluminum oxide, 0.21% iron oxide, 0.01% titanium dioxide, 13.82% calcium oxide, 3.03% magnesium oxide, 2.50% potassium oxide, 1.60% sodium oxide, 2.32% zinc oxide, 1.11% boron oxide, 3.02% barium oxide, and 0.11% ignition loss.
[0082] The chemical composition of the Guangxi Yulin limestone is as follows in percentage by weight: 2.1% silicon oxide, 0.15% aluminum oxide, 0.06% iron oxide, 0.01% titanium dioxide, 56.17% calcium oxide, 0.03% magnesium oxide, 0.11% potassium oxide, 0.09% sodium oxide, and ignition loss is 41.28%.
[0083] The chemical composition of the Guangdong Gaozhou kaolin is as follows in percentage by weight: 53.57% silicon oxide, 35.32% aluminum oxide, 0.15% iron oxide, 0.03% titanium dioxide, 0.17% calcium oxide, 0.06% magnesium oxide, 0.21% potassium oxide, 0.15% sodium oxide, and 10.16% loss on ignition.
[0084] The chemical composition of the clay is as follows in percentage by weight: 62.29% silicon oxide, 23.5% aluminum oxide, 0.19% iron oxide, 0.01% titanium dioxide, 1.35% calcium oxide, 3.21% magnesium oxide, 3.26% potassium oxide, 1.13% sodium oxide, and 5.06% loss on ignition.
[0085] The manufacturing process of the high-gloss transparent crystal glaze of this embodiment includes the following steps:
[0086] (1) putting the glaze raw materials of the above composition into a wet ball mill according to each component, discharging the slurry, and passing through a 250-mesh sieve to obtain a primary material;
[0087] (2) The primary material is passed through a magnetic separator to remove iron, and the glaze fineness is controlled to be between 0.018 on a 10,000-hole sieve, thereby obtaining a high-gloss, translucent crystal glaze.
[0088] The method for using the high-gloss transparent crystal glaze of this embodiment comprises the following steps:
[0089] (1) trimming, hydrating and drying the dry blank to obtain a blank;
[0090] (2) Printing or drawing colored patterns on the blank and drying it;
[0091] (3) using the high-gloss transparent crystal glaze to glaze the blank with the pattern printed on it, the glazing time is 3.5 seconds, the thickness of the glaze layer is controlled at 0.3 mm, and a glaze blank is obtained. The glaze at the foot of the glaze blank is wiped clean, and the glaze blank is checked to be free of defects to obtain a prefabricated glaze blank; the glaze concentration is controlled at 47 degrees Baume, and the glaze water specific gravity is controlled at 1.47;
[0092] (4) The prefabricated glaze blank is placed in a sintering furnace and sintered under multi-stage temperature control. The low temperature stage is the preheating stage of the glaze blank, the kiln temperature is 420°C, and the insulation time is 2 hours. The first medium temperature stage is the weak oxidation stage, the kiln temperature is 840°C, and the insulation time is 1.7 hours. The second medium temperature stage is the strong oxidation stage, the kiln temperature is 1100°C, and the insulation time is 2.7 hours. The high temperature stage is the vitrification stage of the product glaze, the kiln temperature is 1270°C, and the insulation time is 1.7 hours. The rapid cooling stage is the key stage for controlling the product glaze, the kiln temperature is 1280-800°C, and the insulation time is 1.4 hours. The slow cooling stage is the kiln temperature is 800-580°C, and the insulation time is 2.3 hours. After waiting for natural cooling, the firing process is completed and the product is obtained. The use effect is as follows: Figure 3 shown.
[0093] Comparative Example 1
[0094] The transparent glaze used in this comparative example is composed of 20-22 parts by weight of quartz, 3-10 parts of mica, 4-7 parts of Suzhou soil, 2-4 parts of iron hydroxide, 1-2 parts of copper oxide, 15-17 parts of washed mud, 11-13 parts of talc, 3-5 parts of sodium humate, 20-25 parts of bentonite, and 6-8 parts of aluminum powder. The method for using the transparent glaze comprises the following steps:
[0095] (1) trimming, hydrating and drying the dry blank to obtain a blank;
[0096] (2) Printing or drawing colored patterns on the blank and drying it;
[0097] (3) using the high-gloss transparent crystal glaze to glaze the blank with the pattern printed on it, the glazing time is 3.5 seconds, the thickness of the glaze layer is controlled at 0.3 mm, and a glaze blank is obtained. The glaze at the foot of the glaze blank is wiped clean, and the glaze blank is checked to be free of defects to obtain a prefabricated glaze blank; the glaze concentration is controlled at 47 degrees Baume, and the glaze water specific gravity is controlled at 1.47;
[0098] (4) The prefabricated glaze blank is placed in a sintering furnace and sintered in a multi-stage temperature-controlled manner. The low-temperature stage is the preheating stage of the glaze blank, the kiln temperature is 420°C, and the insulation time is 2 hours. The first medium-temperature stage is a weak oxidation stage, the kiln temperature is 840°C, and the insulation time is 1.7 hours. The second medium-temperature stage is a strong oxidation stage, the kiln temperature is 1100°C, and the insulation time is 2.7 hours. The high-temperature stage is the vitrification stage of the product glaze, the kiln temperature is 1270°C, and the insulation time is 1.7 hours. The rapid cooling stage is the key stage for controlling the product glaze, the kiln temperature is 1280-800°C, and the insulation time is 1.4 hours. The slow cooling stage has a kiln temperature of 800-580°C and a insulation time of 2.3 hours. After waiting for natural cooling, the firing process is completed and the product is obtained.
[0099] Comparative Example 2
[0100] The difference from Example 3 is that the prefabricated glaze blank is not sintered by multi-stage temperature control, and the sintering method is as follows:
[0101] The temperature of the firing process is controlled at 1100°C, and the firing cycle is 9 hours; the rapid cooling temperature in the firing process is controlled at 1100-700°C, and the time is controlled at 1 hour.
[0102] Comparative Example 3
[0103] The difference from Example 3 is that the glaze fineness is controlled at 0.03 on the 10,000-hole sieve, the glaze concentration is controlled at 49 degrees Baume, and the glaze water specific gravity is controlled at 1.52.
[0104] The high-gloss transparent crystal glaze of the above-mentioned Examples 1-3 and Comparative Examples 1-3 was used for glazing. After firing, the products were subjected to thermal shock resistance test, lead-cadmium dissolution test, and microwave oven adaptability test. The test results show that the products of Examples 1-3 and Comparative Examples 1-3 did not crack once at 180°C-20°C in the thermal shock resistance test, which meets the national standards. In the lead-cadmium dissolution test, Examples 1-3 and Comparative Example 3 had zero lead-cadmium dissolution, which is far below the requirements of the national industry standards; Comparative Examples 1 and Comparative Example 2 had trace amounts of lead-cadmium dissolution in the lead-cadmium dissolution test, which is below the requirements of the national industry standards. In the microwave oven adaptability test, Examples 1-3, Comparative Examples 1, and Comparative Example 3 did not crack and no arc was generated in one cycle; Comparative Example 2 had cracks in one cycle in the microwave oven adaptability test.
[0105] The products of Examples 1-3 and Comparative Examples 1-3 were evaluated as shown in Table 1 below:
[0106] Table 1
[0107]
[0108]
[0109] It can be seen from the product test and evaluation results of Examples 1-3 and Comparative Examples 1-3 that the potassium feldspar, transparent crystal frit and other materials used in the high-gloss and translucent crystal glaze of the present invention are all locally produced, and the clay is produced by the company itself. The clay on the market is generally 1500-2000 yuan / ton, and the cost of the clay produced by the company itself is 600-1000 / ton. The clay is used in large quantities in the company's products. Self-production greatly reduces the company's production costs. The use of locally produced materials not only helps the local economy, but also saves an average of 500 yuan / ton in freight. The present invention makes full use of local resources, carries out technical research and process transformation. After more than one year of research and debugging, the product achieves the effect of high gloss and high transmittance. The glaze of the product is crystal clear, glass-like and transparent, delicate and bright, with excellent color rendering effect, making the color and pattern of underglaze color bright. The product made of the high-gloss transparent crystal glaze of the present invention is tested for thermal stability: it does not crack at 180-20°C, which meets the national standard; the product is tested for lead and cadmium dissolution: zero lead and cadmium dissolution, and the test result is far lower than the requirement of the national industry standard; the glaze fineness controls the sieve residue to be 0.016-0.02, the glaze concentration is controlled to be 46-48 degrees Baume, and the glaze water specific gravity is controlled to be 1.45-1.48, so that no bubbles are generated on the glaze surface, the turbidity is reduced, and a transparent and delicate texture is achieved.
[0110] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. A high gloss transparent crystal glaze, characterized in that: It is composed of the following mass percentages: 19-22% potassium feldspar from Hezhou, Guangxi, 4-7% limestone from Yulin, Guangxi, 61-65% transparent crystal frit from Kexi City, Guangxi, 3-8% clay, and 3-8% high-altitude soil from Gaozhou, Guangdong; The potassium feldspar in Hezhou, Guangxi is potassium feldspar produced in Hezhou City, Guangxi; the limestone in Yulin, Guangxi is calcined limestone produced in Yulin City, Guangxi; the transparent crystal frit in Cenxi City, Guangxi is transparent crystal frit produced in Cenxi City, Guangxi; and the Gaozhou kaolin is kaolin produced in Gaozhou City, Guangdong.
2. The high gloss transparent crystal glaze according to claim 1, characterized in that: The chemical composition of the Guangxi Hezhou potassium feldspar is as follows in percentage by weight: 69.08% silicon oxide, 17.63% aluminum oxide, 0.12% iron oxide, 0.01% titanium dioxide, 0.51% calcium oxide, 0.13% magnesium oxide, 10.25% potassium oxide, 2.21% sodium oxide, and 0.06% loss on ignition.
3. The high gloss transparent crystal glaze according to claim 1, characterized in that: The chemical composition of the transparent crystal frit in Guxi City, Guangxi Province is as follows in percentage by weight: 65.85% silicon oxide, 6.42% aluminum oxide, 0.21% iron oxide, 0.01% titanium dioxide, 13.82% calcium oxide, 3.03% magnesium oxide, 2.50% potassium oxide, 1.60% sodium oxide, 2.32% zinc oxide, 1.11% boron oxide, 3.02% barium oxide, and 0.11% ignition loss.
4. The high gloss transparent crystal glaze according to claim 1, characterized in that: The chemical composition of the Guangxi Yulin limestone is as follows in percentage by weight: 2.1% silicon oxide, 0.15% aluminum oxide, 0.06% iron oxide, 0.01% titanium dioxide, 56.17% calcium oxide, 0.03% magnesium oxide, 0.11% potassium oxide, 0.09% sodium oxide, and ignition loss of 41.28%.
5. The high gloss transparent crystal glaze according to claim 1, characterized in that: The chemical composition of the Guangdong Gaozhou kaolin is as follows in percentage by weight: 53.57% silicon oxide, 35.32% aluminum oxide, 0.15% iron oxide, 0.03% titanium dioxide, 0.17% calcium oxide, 0.06% magnesium oxide, 0.21% potassium oxide, 0.15% sodium oxide, and 10.16% loss on ignition.
6. The high gloss transparent crystal glaze according to claim 1, characterized in that: The chemical composition of the clay is as follows in percentage by weight: 62.29% silicon oxide, 23.5% aluminum oxide, 0.19% iron oxide, 0.01% titanium dioxide, 1.35% calcium oxide, 3.21% magnesium oxide, 3.26% potassium oxide, 1.13% sodium oxide, and 5.06% loss on ignition.
7. The process for producing a high-gloss transparent crystal glaze according to any one of claims 1 to 6, characterized in that: The steps include: (1) putting the glaze raw materials of the above composition into a wet ball mill according to the percentage of each component, discharging the slurry, and passing through a 200-300 mesh sieve to obtain a primary material; (2) Remove iron from the initial material to obtain a high-gloss, translucent crystal glaze.
8. The method for using any one of the high gloss transparent crystal glazes according to claims 1-6, characterized in that: The steps include: (1) trimming, hydrating and drying the blank to obtain a blank; (2) Printing or drawing colored patterns on the blank and drying it; (3) dipping the blank with the pattern printed thereon with the high-gloss transparent crystal glaze for 3-4 seconds to obtain a glaze blank, wiping off the glaze accumulated at the foot of the glaze blank, and checking that the glaze blank has no defects to obtain a prefabricated glaze blank; (4) placing the prefabricated glaze blank into a sintering furnace, and sintering the prefabricated glaze blank in a multi-stage temperature-controlled sintering process, including a low temperature stage, a first medium temperature stage, a second medium temperature stage, a high temperature stage, a rapid cooling stage, and a slow cooling stage; the sintering process is performed in an oxidizing atmosphere; (5) The sintered glaze blanks are graded and numbered, and packaged for shipment.
9. The process for producing a high-gloss transparent crystal glaze according to claim 7, characterized in that: The multi-stage temperature control process specifically includes: (1) Low temperature stage: the preheating stage of the glaze blank, the kiln temperature is 350-480℃, and the insulation time is 1.8-2.2h; (2) The first medium temperature stage is a weak oxidation stage, the kiln temperature is 800-870℃, and the insulation time is 1.5-2.0h; (3) The second medium temperature stage is the strong oxidation stage, the kiln temperature is 980-1050℃, and the insulation time is 2.5-3.0h; (4) High temperature stage, which is the stage of product glaze vitrification, the kiln temperature is 1260-1280℃, and the insulation time is 1.5-2.0h; (5) Rapid cooling stage is the key stage for controlling the glaze surface of the product. The kiln temperature is 1280-800℃ and the control time is 1.2-1.5h; (6) Slow cooling stage, the kiln temperature is 800-580℃, and the control time is 2.0-2.5h; (7) Wait for natural cooling to complete the firing process.
10. The high gloss transparent crystal glaze according to claim 1, characterized in that: The glaze fineness is controlled to have a sieve residue between 0.016 and 0.02; the glaze concentration is controlled to be between 46 and 48 degrees Baume; and the glaze water specific gravity is controlled to be between 1.45 and 1.48.
